2014
DOI: 10.1016/j.cis.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Recent theoretical advances in elasticity of membranes following Helfrich's spontaneous curvature model

Abstract: Recent theoretical advances in elasticity of membranes following Helfrich's famous spontaneous curvature model are summarized in this review. The governing equations describing equilibrium configurations of lipid vesicles, lipid membranes with free edges, and chiral lipid membranes are presented. Several analytic solutions to these equations and their corresponding configurations are demonstrated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 122 publications
(236 reference statements)
0
36
0
1
Order By: Relevance
“…Furthermore, because they are codimension-1 branes, it means that the extrinsic curvature tensor only has one direction and hence a term proportional to K, where we have omitted the index i, can be added to (2) as well as terms proportional to worldvolume derivatives of K [5,18]. A recent review of different models for biophysical membranes and their usage can be found in [19]. Despite the fact that the black branes that we will consider are generically of codimension higher than one, the black ring configuration that we will analyse in detail is described by a two-dimensional membrane with only one extrinsic curvature component and hence effectively behaving like a fluid membrane of codimension-1.…”
Section: Arxiv:14026330v2 [Hep-th] 26 Nov 2014mentioning
confidence: 99%
“…Furthermore, because they are codimension-1 branes, it means that the extrinsic curvature tensor only has one direction and hence a term proportional to K, where we have omitted the index i, can be added to (2) as well as terms proportional to worldvolume derivatives of K [5,18]. A recent review of different models for biophysical membranes and their usage can be found in [19]. Despite the fact that the black branes that we will consider are generically of codimension higher than one, the black ring configuration that we will analyse in detail is described by a two-dimensional membrane with only one extrinsic curvature component and hence effectively behaving like a fluid membrane of codimension-1.…”
Section: Arxiv:14026330v2 [Hep-th] 26 Nov 2014mentioning
confidence: 99%
“…In this simplification, the variational principle can be interpreted as an analogue of Hamilton's principle of classical mechanics, with the free energy interpreted as an action describing the trajectory of a fictitious particle, and the parameter along the surface contour playing the role of a time parameter [4,27,28]. The problem is reduced to a finite number of degrees of freedom, but it is still highly non trivial, involving higher derivative non-linear ordinary differential equations [29]. In field theory, a different type of simplification is obtained by the use of the height, or Monge, representation, where the surface is represented by a height function, that depends on the two coordinates of a planar reference configuration [5].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of genus-0 vesicles has been intensively investigated, both experimentally and theoretically [14][15][16][17][18][19][20][21][22][23]. Discocyte, prolate, and stomatocyte, can be reproduced by the minimization of bending energy with area and volume constraints.…”
Section: Introductionmentioning
confidence: 99%